Paper 56: Defining Clinically Significant Outcomes After Gluteus Medius Repair at 5-Years. Issue 7 (30th July 2022) - Sivasundaram, Lakshmanan; Browning, Robert; Holland, Tai; Paul, Katlynn; Nho, Shane; Rice, Morgan
Objectives: To define minimal clinically important difference (MCID) and patient acceptable symptom state (PASS) at a minimum of 5-years for patients undergoing endoscopic and open gluteus medius repair. Methods: A retrospective review was performed of prospectively collected data from all patients undergoing primary open or endoscopic repair of gluteus medius tears between January 2012 and December 2015 with a minimum 5-years follow-up. Patient data collected included patient demographics, preoperative clinical function scores, and pre and postoperative patient-reported outcomes (PROs). Patient reported outcome measures included the Hip Outcome Score Activities of Daily Living (HOS-ADL) and Sports Subscale (HOS-SS), Modified Harris Hip Score (mHHS) and Internation Hip Outcome Tool 12 questions (iHOT-12). The minimal clinically important difference (MCID) values were calculated for each PRO using the distribution method while PASS was determined via the anchor-based method utilizing ROC curves and Youden's index using SPSS Statistics (Version 27, IBM, Armonk, NY). Results: A total of 46 patients were included in the study. A majority of patients were female (91.3%), with an average age and BMI of 61.26 ± 9.74 and 27.42 ± 6.02, respectively. Differences in preoperative and 5-year postoperative PROs were statistically significant for each of the four measures (p<0.001). The MCID threshold values for the Hip Outcome Score-Activities of Daily Living (HOS-ADL), Sport-Specific (HOS-SS) subscale, modified Harris Hip Score (mHHS), and the international Hip Outcome Tool-12 (iHOT) were calculated to be 13.1, 14.5, 12.6 and 11.2 respectively. The PASS scores of HOS-ADL, HOS-SS, mHHS and iHOT were calculated to be 85.6, 79.7, 68.2 and 60.5 respectively. In addition, 86.1% of patients achieved either MCID or PASS postoperatively, with 90.9% and 69.8% reaching at least 1 threshold score for achieving MCID and PASS respectively, and 69.7% achieving both any MCID and any PASS. Conclusions: In patients undergoing open or endoscopic gluteus medius repair, our study defines MCID and PASS at mid-term follow-up. A majority of patients achieved any MCID (90.9%) and any PASS (69.7%) at 5-years postoperatively.